Strategic foresight analysis for high impact interventions in agriculture and food security - Girvetz, Evan Hartunian; Osiemo, Jamleck; Prager, Steven D. (International Center for Tropical Agriculture, 2017)
A mix of demographic, technological, climate and environmental changes make anticipating and planning the future a complex - but critical step - to increase our food supply while sustaining natural resources. Successful interventions which meet these twin objectives are a priority for governments, multi-lateral banks, NGOs, and the private sector. It is vital that we articulate the potential impacts of climate change, different interventions, and policy decisions on the most strategic areas of investment to achieve the best economic and social benefits. The question remains: how to articulate these complex factors to support policy and decision making by governments and organizations?